Thermodynamics of oxygen-containing intermediates and their role in coal spontaneous combustion - Li, Jin-liang; Lu, Wei; Li, Jin-hu; Zhang, Qinsong; Zhuo, Hui (Energy (Oxford), 2022)
Oxygen-containing intermediates (OCIs) play an important role in low-temperature oxidation of coal. However, since they are in a dynamic intermediate state, it is difficult to test their thermodynamic properties, and their mechanism of action in coal spontaneous combustion(CSC) are not clear. Therefore, this paper proposed a method to measure the thermodynamics of the OCIs. Furthermore, the reasons for the variation laws of the thermodynamics of the OCIs and their mechanisms of action in CSC were investigated from both macro and micro perspectives. According to the experimental results, thermodynamic parameters of the OCIs can be obtained using the proposed method. And the heating rate of OCIs calculated by the mathematical model based on this method is closer to the total rate of coal oxidation before 70 °C, indicating that OCIs play an important role in the starting process of CSC. Besides, the activation energy of OCIs presents different variation characteristics in different stages. The segmentation can be attributed to the stability of OCIs, which is also critical to the prevention and control of CSC. Hence, the risk of CSC can be reduced by improving the stability of OCIs. •A method to quantitatively calculate the thermodynamic parameters of oxygen-containing intermediates (OCIs) was established.•From the point of view of heat, OCIs play an important role in the starting process of coal spontaneous combustion (CSC).•The activation energy of OCIs has obvious segmentation.•The cumulative production and decomposition threshold of peroxide are the key factors affecting CSC.